Analisa Pelayanan Pelanganggan Elektronik Bengkel Kong Xi Motor - Aryanto Nur; Seiren Febriyana; Khaerul Imam Nasution; Sultan Afrilla; Faizal Zidni (Journal Of Informatics And Busisnes, 2024)
A workshop is a place used to perform various types of repair, maintenance, and modification work on motor vehicles. In a workshop, skilled mechanics will perform various types of work ranging from changing engine oil, repairing brake systems, to modifying the exterior and interior of the vehicle. Workshops are usually equipped with complete equipment and work tools to support the vehicle repair process. Generally, workshops use a manual system in their operations, but, in this modern era, many workshops have used electronic service systems. The purpose of writing this journal is to determine trends, patterns, factors that influence, and anticipation of the advantages and disadvantages of developing web-based services in workshops. The study uses a quantitative method with a survey data collection method. ustomer satisfaction is very important to retain customers and business sustainability. Customer perception of service is greatly influenced by ease of service access, speed of response, and availability of information. Kong Xi Motor is one of the motorcycle repair shops in Bogor Regency, precisely in Kp. Pasir Gaok RT 05/01, Bogor. Kong Xi Motor Workshop still uses manual bookkeeping, which is at risk of damage and loss. With the existence of an information system in the form of a website, it can be easy to manage information data about the workshop. In developing this information system, we chose the qualitative method and the waterfall method.